1995
DOI: 10.1007/bf01876734
|View full text |Cite
|
Sign up to set email alerts
|

A treatment program for children with sexual behavior problems

Abstract: This paper discusses the problems and treatment of children with sexual behavior problems.These children coerce, intimidate or force other children by threats of physical harm to comply with their sexual requests,frequently a reenactment of their own experiences.This paper describes a comprehensive therapeutic foster care approach to these children.Many clinicians as well as researchers, tend to minimize the seriousness of young sexual offenders, describing their behavior as innocent sex play, experimentation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…“The participant not living with the natural (biological) mother until he or she was at least 16 years old” and “have ever had a stepfather or adoptive father until he or she was at least 16 years old” were identified in this study as factors predicting child sexual abuse. Some authors have indicated that parental divorce (Rickards, 1997; Henning et al , 1997;Klein & Janoff‐Bulman, 1996; Clifford & Clark, 1995; Engels et al , 1994) and the presence of a foster‐parent (Landy & Munro, 1998; Lipton, 1997;Ray et al , 1995;Treacy, 1995; Shah, 1976) are aspects of parental physical absence that contribute to child abuse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…“The participant not living with the natural (biological) mother until he or she was at least 16 years old” and “have ever had a stepfather or adoptive father until he or she was at least 16 years old” were identified in this study as factors predicting child sexual abuse. Some authors have indicated that parental divorce (Rickards, 1997; Henning et al , 1997;Klein & Janoff‐Bulman, 1996; Clifford & Clark, 1995; Engels et al , 1994) and the presence of a foster‐parent (Landy & Munro, 1998; Lipton, 1997;Ray et al , 1995;Treacy, 1995; Shah, 1976) are aspects of parental physical absence that contribute to child abuse.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have indicated that some aspects of parental physical absence can contribute to child abuse. Some of those aspects are parental divorce (Rickards, 1997;Henning, Leitenberg, Coffey, Bennett & Jankowski, 1997; Klein & Janoff‐Bulman, 1996; Clifford & Clark, 1995; Engels, Moisan & Harris, 1994), the presence of a foster parent (Landy & Munro, 1998;Lipton, 1997;Ray, Smith, Peterson, Gray, Jennifer & Meyia, 1995;Treacy, 1995; Shah, 1976), placing a child in a group home (Bosch, 1997; Anolik & Stevens, 1998; Barth, Courtney, Berrick & Albert, 1994), and placing a child in juvenile detention (Grossman, 1997;Dembo, Williams & Schmeidler, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Two further US studies considered the use of treatment foster care for children with sexual behaviour problems. A small-scale study of the Sexually Reactive Youth Program reported that, after 18 months in the programme, none of the children were displaying inappropriate sexual behaviour (Ray et al 1995). However, four children had documented incidents of further inappropriate sexual behaviour early into the therapy and interviews after the programme was complete revealed that two children displayed inappropriate sexual behaviour when under stress.…”
Section: Interventions For Preventing and Managing Peer Violence In Fmentioning
confidence: 99%
“…There has been gathering recognition here in the US that foster care may present numerous and significant advantages over residential or institutional care for these special clients for reasons of intervention quality as well as cost (Barth, 2001). One of the first studies here to report specifically on the effects of a foster care program for young children with problem sexual behaviors concerned itself with the global behavior progress of its clients rather than with their sexual behavior-specific improvement (Ray et al, 1995), but that study opened a conceptual door.More recently, Ownbey, Jones, Judkins, Everidge, and Timbers (2001) have reported the effects of a specialized program of foster care on both the frequency of problem sexual behavior and foster care giver estimates of the propensity to re-offend (a measure of treatment internalization) of six initial clients referred to a treatment-intensive foster program for sexually reactive children and sexually aggressive pre-adolescents. That study concerned itself more with preliminary client outcomes than with the details of the program elements that were brought to bear on the clients whose data were presented.…”
mentioning
confidence: 98%
“…There has been gathering recognition here in the US that foster care may present numerous and significant advantages over residential or institutional care for these special clients for reasons of intervention quality as well as cost (Barth, 2001). One of the first studies here to report specifically on the effects of a foster care program for young children with problem sexual behaviors concerned itself with the global behavior progress of its clients rather than with their sexual behavior-specific improvement (Ray et al, 1995), but that study opened a conceptual door.…”
mentioning
confidence: 98%